Prenatal Alcohol Exposure and Interhemispheric Transfer of Tactile Information: Detroit and Cape Town Findings - Dodge, Neil C. (2009)
BACKGROUND: Previous research has demonstrated that heavy prenatal alcohol exposure affects the size and shape of the corpus callosum (CC) and compromises interhemispheric transfer of information. The aim of this study was to confirm the previous reports of poorer performance on a finger localization test (FLT) of interhemispheric transfer in a cohort of heavily exposed children and to extend these findings to a cohort of moderately exposed young adults. METHODS: In Study 1, the FLT was administered to 40 heavily-exposed and 23 non-exposed children from the Cape Coloured community of Cape Town, South Africa, who were evaluated for fetal alcohol syndrome (FAS) dysmorphology and growth. Anatomical images of the CC were obtained using structural MRI on a subset of these children. In Study 2, the FLT was administered to a cohort of 85 moderate-to heavily exposed young adults participating in a 19-year follow-up assessment of the Detroit Prenatal Alcohol Exposure cohort, whose alcohol exposure had been ascertained prospectively during gestation. RESULTS: In Study 1, children with FAS showed more transfer-related errors than controls after adjustment for confounding, and increased transfer-related errors were associated with volume reductions in the isthmus and splenium of the CC. In Study 2, transfer-related errors were associated with quantity of alcohol consumed per occasion during pregnancy. More errors were made if the mother reported binge drinking (≥ 5 standard drinks) during pregnancy than if she drank regularly (M ≥ 1 drink/per day) without binge drinking. CONCLUSIONS: These findings confirm a previous report of impaired interhemispheric transfer of tactile information in children heavily exposed to alcohol in utero and extend these findings to show that these deficits are also seen in more moderately exposed individuals, particularly those exposed to binge-like pregnancy drinking.